Universities and The Locational Dynamics of Academic Entrepreneurship: An Approach for The State of São Paulo, Brazil - Scorsatto, Filipe (2019)
Purpose - This research aims to investigate the dynamics of location of academic entrepreneurs in the State of São Paulo, Brazil, and its association with the respective universities of origin.Method - A total of 1,082 PIPE/FAPESP projects were analyzed between 1998 and 2017, allowing the construction of heatmaps that demonstrate consistent patterns of geographic distribution of knowledge-intensive academic entrepreneurship in the State of São Paulo.Main results - While research-intensive public universities play a leading role in the generation and retention of entrepreneurs at the local level, the distance from developed markets significantly reduces the concentration of spin offs in regions.Theoretical/methodological contributions – Findings have implications for the notion that universities’ campuses can trigger levels of regional development, since the causal relationships in this process seem to be linked to both endogenous factors and processes exogenous to the university.Relevance/originality - Issues involved in this analysis include topics of central interest in the search for a deeper understanding of the evolutionary dynamics of entrepreneurship ecosystems in the Brazilian context.